Social Media Marketing Strategy Through Instagram At Hotel Santika Bengkulu - Denny Wiryadhana; Ahmad Soleh; Silke Sachanovrissa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The development of marketing through social media is increasing rapidly and has become a trend and necessity in the present. Hotel Santika Bengkulu uses social media marketing as the main means to interact, communicate, promote products & services and build brand image to its target consumers. This study aims to determine the application of social media marketing strategies Instagram by analyzing 4 indicators of social media influence as a marketing method and to find out whether the strategy is running well and meets the objectives. The research method is descriptive qualitative approach uses theoretical studies, observations, interview and questionnaires whose results are analyzed by triangulation method. The study results revealed that Hotel Santika Bengkulu has carried out social media marketing activities to a general audience where in Context all the criteria have been carried out and running well, it needs to be improved in the aspects of strategic planning and action plans. In Communication, it has been done, only efforts need to be made to maximize the features on Instagram. In the Collaboration, the efforts made are on track to increase collaboration from followers. In Connection, it is necessary to increase the frequency and uploads concept that are more appealing to improve relationships with users and followers. From the achievement of the objectives of implementing Instagram for specific consumers, it focuses more on brand awareness aspects and still needs improvement in the aspects of engagement, customer service and lead generation .